Geographical distribution and notes on the nests of the “uruçu-do-chão” bee, Melipona (Melikerria) quinquefasciata Lepeletier, in Bahia, North-eastern Brazil - Castro, Marina Siqueira de; Trindade-Santos, Matheus Eduardo; Ramos, Ramon Lima; Spineli, Amia Carina; Leal, Synara Mattos (EntomoBrasilis, 2023)
The Neotropical genus of stingless bees Melipona Illiger, 1806 is exclusive to Tropical America and has its greatest diversity in South America, with about 74 described species. In Bahia, there is an occurrence record for 12 species of Melipona, distributed in four subgenera. Among the Melipona (Melikerria) that occur in Bahia, we highlight Melipona (Melikerria) quinquefasciata Lepeletier, 1836. Although widely distributed in Brazil, its underground nesting habit associated with its preference for high altitude areas, make the species extremely vulnerable. This work sought to describe nests and map the occurrence of this species for the State of Bahia, since its record is limited to areas of Chapada Diamantina. Knowledge about the biogeography of the species is extremely important, strengthening its sustainable creation that respects the area of ​​occurrence of the species, as well as seeking alternatives and public policies for sustainable conservation, since its area of ​​occurrence is extremely vulnerable to the expansion of the agricultural frontier in the State.